2016
DOI: 10.1016/j.micres.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of drought stress tolerance in crops by plant growth promoting rhizobacteria

Abstract: Drought is one of the major constraints on agricultural productivity worldwide and is likely to further increase. Several adaptations and mitigation strategies are required to cope with drought stress. Plant growth promoting rhizobacteria (PGPR) could play a significant role in alleviation of drought stress in plants. These beneficial microorganisms colonize the rhizosphere/endo-rhizosphere of plants and impart drought tolerance by producing exopolysaccharides (EPS), phytohormones, 1-aminocyclopropane- 1-carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
446
0
21

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 937 publications
(528 citation statements)
references
References 112 publications
10
446
0
21
Order By: Relevance
“…Hence, it was observed that inoculation with PGPR strains alleviated the plant drought stress, increasing plant growth and yield, and different strains performed differently (Sarma et al 2012;Vurukonda et al 2016). It was also evident from the result that IAA production was stimulated by 5-6× in plants as compared to rhizosphere soil when inoculated with Bacillus pumilus and Bacillus cereus, in the presence of L-tryptophan under induced drought stress.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hence, it was observed that inoculation with PGPR strains alleviated the plant drought stress, increasing plant growth and yield, and different strains performed differently (Sarma et al 2012;Vurukonda et al 2016). It was also evident from the result that IAA production was stimulated by 5-6× in plants as compared to rhizosphere soil when inoculated with Bacillus pumilus and Bacillus cereus, in the presence of L-tryptophan under induced drought stress.…”
Section: Discussionmentioning
confidence: 88%
“…These findings are in accordance with those of Armada et al (2014) and Gusain et al (2015), who reported an increased accumulation of compatible solutes like proline, which is an important adaptation mechanism for metabolic adjustment of plants grown under drought stress. Moreover, PGPR inoculation have been reported to increase plant biomass and photosynthetic pigments (Chl a, b and carotenoids) under drought stress as compared to uninoculated control (Vurukonda et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…PGPR are the main components of soil biodiversity and play a key role in enhancing soil nutrients and moisture content as they colonize the rhizosphere of plants and produce various substances including exopolysaccharides, phytohormones, aminocyclopropane-1-carboxylate deaminase, induce accumulation of osmolytes, antioxidant enzymes and adopt root morphology to drought stress (Vurukonda et al 2016). PGPR appear to act synergistically to augment the chlorophyll content of the leaves and the sensitive variety was more responsive to PGR and PGPR.…”
Section: Discussionmentioning
confidence: 99%
“…The rhizosphere and associated microbiota play critical roles in controlling the ability of plants and plant ecosystems to cope with drought. PGPRs colonize the rhizosphere/endo-rhizosphere of plants and confer drought tolerance by: (i) producing exopolysaccharides (EPS), 1-aminocyclopropane-1-carboxylate (ACC) deaminase, VOCs, phytohormones like abscisic acid (ABA), gibberellic acid, cytokinins, and indole-3-acetic acid (IAA); (ii) inducing accumulation of osmolytes and antioxidants; and (iii) regulation of stress-responsive genes and alteration in root morphology (Vurukonda et al, 2016a). For example, IAA-producing Azospirillum spp.…”
Section: Droughtmentioning
confidence: 99%